Tres cuerpos y un solo goce verdadero (2009)
ABSTRACT: Talking about body from a positivist perspective means the appearance of the body-soul duality; nevertheless, from an analytical viewpoint, we understand that the body, as a receptacle of the human, is paradoxically unrelated and ominous to ourselves. So, to apprehend such a concept it is necessary a topology of it in order to be different from being and entity. The text analyses what makes psychoanalysis different from other practices: its interpretation of the body as inhabited by the libido and its chance of pleasure mediated by the appearance of the signifier, going through the desire, the request and the sexuality; moments that, as well as psychism, inaugurate a real, symbolic and imaginary body as logs allowing its unification and the appearance of a fourth differentiating element, the enjoying substance and its topologic tying function.